Ultra-high Q even eigenmode resonance in terahertz metamaterials - Al-Naib, Ibraheem (2015)
We report the simultaneous excitation of the odd and the even eigenmode resonances in a periodic array of square split-ring resonators, with four resonators per unit cell. When the electric field is parallel to their gaps, only the two well-studied odd eigenmodes are excited. As the resonators are rotated relative to one another, we observe the emergence and excitation of an extremely sharp even eigenmode. In uncoupled split-ring resonators, this even eigenmode is typically radiative in nature with a broad resonance linewidth and low Q-factor. However, in our coupled system, for specific range of rotation angles, our simulations revealed a remarkably high quality factor (Q ∼ 100) for this eigenmode, which has sub-radiant characteristics. This type of quad-supercell metamaterial offers the advantage of enabling access to all the three distinct resonance features of the split-ring resonator, which consists of two odd eigenmodes in addition to the high-Q even eigenmode, which could be exploited for high performance multiband filters and absorbers. The high Q even eigenmode could find applications in designing label free bio-sensors and for studying the enhanced light matter interaction effects.